2013
DOI: 10.1016/j.bbamcr.2013.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Direct association of the reticulon protein RTN1A with the ryanodine receptor 2 in neurons

Abstract: RTN1A is a reticulon protein with predominant localization in the endoplasmic reticulum (ER). It was previously shown that RTN1A is expressed in neurons of the mammalian central nervous system but functional information remains sparse. To elucidate the neuronal function of RTN1A, we chose to focus our investigation on identifying possible novel binding partners specifically interacting with the unique N-terminus of RTN1A. Using a nonbiased approach involving GST pull-downs and MS analysis, we identified the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 66 publications
5
10
0
Order By: Relevance
“…Previous studies have demonstrated that RYR plays an important role in Purkinje cell maturation. 44 , 46 , 47 Dot blot analysis revealed that RYR levels were also upregulated in the hOEC transplantation group ( Fig. 3B ).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous studies have demonstrated that RYR plays an important role in Purkinje cell maturation. 44 , 46 , 47 Dot blot analysis revealed that RYR levels were also upregulated in the hOEC transplantation group ( Fig. 3B ).…”
Section: Resultsmentioning
confidence: 90%
“…This improvement might protect the Purkinje cells from degeneration. On the other hand, it has been reported that increased TPH2 and RYR 44 , 46 , 47 were associated with the maturation of Purkinje cells, thus indicating that the factors might have aided in the maturation of many progenitor or immature cells. We further observed that the number of Purkinje cells increased posttransplantation with hOECs ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount and type of antibodies were the same as indicated above. In addition, we used rabbit anti-RTN1-A antibody [24], 1:10000 dilution), mouse anti-Apg-2 (Santa Cruz Biotechnology; sc-365366, 1:200 dilution) and mouse anti-Hsp105 (Santa Cruz Biotechnology; sc-74550, 1:200 dilution) antibodies for Western blotting.…”
Section: Methodsmentioning
confidence: 99%
“…Reticulon 1A also directly associates with ryanodine receptor (RyR) 2, regulating intracellular calcium buffering by reducing oscillations mediated by RyR2 on rat Purkinje neurons (Kaya et al, ). Reticulon 1A may additionally raise the surface/volume ratio of the ER favoring calcium release.…”
Section: The Structure Of the Er In Axonsmentioning
confidence: 99%